Are B chromosomes useful for crop improvement?. Issue 2 (1st March 2019) - Jones, Neil; Ruban, Alevtina
Societal Impact Statement: Ensuring the sustainable production of food within the context of an increasing world population is a huge challenge facing humankind. Here we review the existence of additional, non‐essential chromosomes, known as B chromosomes, and consider their potential usefulness for crop improvement. These enigmatic chromosomes have long fascinated scientists and although their origin and function in plants is somewhat obscure, new research is beginning to shed light on these mysterious chromosomes. This work suggests that B chromosomes may be useful for crop improvement, particularly in grasses, where they show promise as a mechanism to introduce new genes, which could potentially help us to produce more efficient crops. Summary The question of the usefulness of supernumerary B chromosomes (Bs) has long fascinated cytogeneticists. Since their discovery in 1907 thousands of species with Bs have been discovered, but their function in the genetics system remains enigmatic, from their origin, evolution, and adaptive significance, as well as their molecular structure and organization. New research is beginning to answer some of these tantalizing questions. Here, we summarize the known data and conclude that Bs are potentially useful, but only in a few known cases, especially in the grasses, and notably in terms of their engineering as plant artificial chromosomes (mini‐chromosomes) to carry whole suites of transgenes outside of, and free from interference with, the normal genome. Abstract : Ensuring the sustainable production of food within the context of an increasing world population is a huge challenge facing humankind. Here we review the existence of additional, non‐essential chromosomes, known as B chromosomes, and consider their potential usefulness for crop improvement. These enigmatic chromosomes have long fascinated scientists and although their origin and function in plants is somewhat obscure, new research is beginning to shed light on these mysterious chromosomes. This work suggests that B chromosomes may be useful for crop improvement, particularly in grasses, where they show promise as a mechanism to introduce new genes, which could potentially help us to produce more efficient crops.